C’est en youtubant que l’on devient youtubeur ! Spelling and Words Derived from Social MediaNames in the General French Corpus - Holeš, Jan (Verbum, 2025)
The article deals with spelling and derivatives of the names of the most popular social media in France, namely Facebook, YouTube, WhatsApp, Instagram, TikTok, and Snapchat, as they are used in the general corpus of texts published on the Internet. These names appear in a wide variety of forms, alternating initial uppercase and lowercase letters, inserted letters, hyphens and spaces between their components. In addition, the article analyses the frequency of the words derived from these names, in the same corpus, including particularly the nouns designating the users of these media, the verbs designating on the media, and the adjectives relating to the objects published in the given medium. SketchEngine, an online text analysis tool that allows identifying what is typical and frequent in a language, and the French corpus frTenTen23, made up of texts collected on the Internet, were used for the analysis. The article provides concrete statistics for these forms and derivatives
Keywords: neologisms; social media; French language; trademarks; derivation; spelling